The Role of Paradiplomatic Actors in the G20 Green Bond and Green Sukuk Agenda: A Local Political Analysis of Provincial and Municipal Governments in Indonesia - Dhea Puspita Wardani; Stivani Ismawira Sinambela; Kasih Setia Zendrato (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
- This qualitative study examines the involvement of paradiplomatic actors in implementing green bond and green sukuk instruments promoted by the G20 Sustainable Finance Working Group (SFWG). Specifically, the study focuses on the local political dimensions of this process, with particular attention to the roles of provincial governments, namely DKI Jakarta and Jawa Barat, and selected municipal governments, including Surabaya and Bandung. The analysis encompasses the political agency of elected governors and mayors, regional legislative councils (DPRD) in approving green budget allocations (APBD), regional planning agencies (BAPPEDA) in identifying eligible green projects, and local policy networks embedded within these subnational structures. Through content analysis of policy documents, literature, and regulatory frameworks from 2018 to 2024, the research highlights the vital role of global city networks like C40 Cities and UCLG-ASPAC. These networks act as strategic bridges, translating global climate commitments into concrete subnational actions. As tangible evidence, Indonesia's cumulative sovereign green sukuk issuance reached USD 9.6 billion (2018–2023), channelling resources into six key sectors: renewable energy (38.5%), sustainable transport (28.3%), waste management (12.4%), water and sanitation (10.8%), climate adaptation (6.2%), and energy efficiency (3.8%). These allocations collectively generated 130,316.39 tonnes of CO₂ equivalent reductions per year by 2022. Nevertheless, efforts to scale up green financing remain hindered by structural issues—resource disparities, fragile DPRD-central government coordination, and overlapping interjurisdictional regulations. To optimize the impact of green finance locally, governance improvements, regulatory synchronization, and capacity building for practitioners are essential. This study recommends enforcing clear national green taxonomy standards, transparent reporting mechanisms, targeted fiscal incentives, and measurable local performance indicat